-7(x+2)+4x+7=6x+9

Simple and best practice solution for -7(x+2)+4x+7=6x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(x+2)+4x+7=6x+9 equation:


-7(x+2)+4x+7=6x+9

We simplify the equation to the form, which is simple to understand
-7(x+2)+4x+7=6x+9

Reorder the terms in parentheses
+(-7x-14)+4x+7=6x+9

Remove unnecessary parentheses
-7x-14+4x+7=+6x+9

We move all terms containing x to the left and all other terms to the right.
-7x+4x-6x=+9+14-7

We simplify left and right side of the equation.
-9x=+16

We divide both sides of the equation by -9 to get x.
x=-1.77777777778

See similar equations:

| 320=144t-16t^2 | | 6x+35=16-75 | | 10[z-(9z+18)+10]=5(z+1) | | p+7/p+2p/p+3 | | 2x+66=4x+32 | | -6p-3(5-5p)=4(p-3)-43 | | =(x^2-12x+40)(x^2+6x+10) | | 3x^2+5x+6= | | 7x^2+30x-8=0 | | 8+5t=2t+14 | | 738-67x=6250 | | x/5-4=x/2+8 | | (-(1/2))^(-2) | | b+24=60 | | -9-5=5x+6-4x | | 18m^2-180mn+50N^2=0 | | x+.0507x=2300 | | 2z-1=180 | | x/24=-14+3 | | 3z=16-25 | | 16/38 | | B=ha | | (2x-3)(5x^2-6x+7)= | | 2v^2-v=6 | | C/g=Q+v/v | | -5(9x+9)= | | 8c+9c+2c-1= | | (3x^4)(2x^2)= | | 5/30t-24/30=6/30 | | 15a^2-6a^3= | | =4x^2-19x+12 | | Xsquared+7x-44=0 |

Equations solver categories